2017
DOI: 10.1002/2017wr020457
|View full text |Cite
|
Sign up to set email alerts
|

Dam removal: Listening in

Abstract: Dam removal is widely used as an approach for river restoration in the United States. The increase in dam removals—particularly large dams—and associated dam‐removal studies over the last few decades motivated a working group at the USGS John Wesley Powell Center for Analysis and Synthesis to review and synthesize available studies of dam removals and their findings. Based on dam removals thus far, some general conclusions have emerged: (1) physical responses are typically fast, with the rate of sediment erosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
193
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 199 publications
(197 citation statements)
references
References 144 publications
(306 reference statements)
4
193
0
Order By: Relevance
“…); after dam removal, higher‐salinity habitats migrated seaward from the historic estuary complex to the newly formed delta (Foley et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…); after dam removal, higher‐salinity habitats migrated seaward from the historic estuary complex to the newly formed delta (Foley et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…; Foley et al. ), and restoring connectivity can increase the abundance, spatial distribution, and life history diversity of migratory fishes (Hitt et al. ; Pess et al.…”
mentioning
confidence: 99%
“…The removal of barriers, such as dams and culverts, has become a commonly used approach in river restoration to re‐establish the connectivity of river flow, sediment, and species movement (Foley et al. 2017a). These removals have resulted in increases in native species richness, diversity, and productivity (Foley et al.…”
Section: Examples Of How Spatial Scale Is Relevant To Barrier Removalmentioning
confidence: 99%
“…These removals have resulted in increases in native species richness, diversity, and productivity (Foley et al. 2017a). Barrier removal is also used to restore commercially important or threatened migratory fish, such as salmonids (family Salmonidae), alosines (family Clupeidae), sturgeons (family Acipenseridae), Sea Lamprey Petromyzon marinus , and freshwater eels Anguilla spp., by improving the connectivity between feeding and spawning habitats (Pess et al.…”
Section: Examples Of How Spatial Scale Is Relevant To Barrier Removalmentioning
confidence: 99%
“…We have learned much by analyzing fluvial responses to past events. Studies have shown that geomorphic responses to fluvial disturbances (1) relax over varying timescales but can persist for years to decades, even centuries; (2) can be both acute and gradual; (3) are influenced by many factors including hillslope‐channel coupling, physical linkages among channel reaches, and hydrological regimes; (4) can follow many trajectories; (5) are intricately intertwined with ecological recovery; and (6) that systems may not return to predisturbance states (e.g., Bellmore et al, ; Cluer & Thorne, ; East et al, ; Foley et al, ; Gellis et al, ; Gran et al, , ; James, ; James & Lecce, ; Kasai, ; Kasai et al, ; Major et al, ; Moody & Meade, , ; Pierson & Major, ; Schumm, ; Swanson & Major, ). But we can further exploit records of physical responses to profound fluvial disturbances to gain richer geomorphic insights.…”
Section: Introductionmentioning
confidence: 99%